2017
DOI: 10.1038/srep42907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmentally-relevant concentrations of nonylphenol on sexual differentiation in zebrafish: a multi-generational study

Abstract: Nonylphenol (NP) is a well-known endocrine disrupting chemical (EDC) that is persistently and frequently found in rivers, tap water, lakes and sea 1,2 . NP, arising from the degradation of NP ethoxylates, is a highly cost-effective surfactant used in industrial, commercial and household applications 3,4 . NP is a widely distributed in aquatic system. The concentration of NP ranges from undetected to 33.2 μ g·L −1 in lakes and rivers 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…No incidence of testis-ova was found neither in the control group nor in 10 μgL -1 exposed fish. Sex ratio in the multigeneration exposed to NP was affected, where the proportion of females accounted for 80% (36 females) in 20 μgL −1 of NP, however, treatment with 2 μgL −1 and 200 μgL −1 did not show any significant difference from the control (Sun et al, 2017). In Contrary, rainbow trout (Oncorhynchus mykiss) exposed to 1.05 and 10.17 µg NP L -1 from the egg stage until 1 year of age did not induce testis-ova or lead to alter the sex ratios when compared with the control group (Ackermann et al, 2002).…”
Section: Sc Sc Szmentioning
confidence: 90%
See 1 more Smart Citation
“…No incidence of testis-ova was found neither in the control group nor in 10 μgL -1 exposed fish. Sex ratio in the multigeneration exposed to NP was affected, where the proportion of females accounted for 80% (36 females) in 20 μgL −1 of NP, however, treatment with 2 μgL −1 and 200 μgL −1 did not show any significant difference from the control (Sun et al, 2017). In Contrary, rainbow trout (Oncorhynchus mykiss) exposed to 1.05 and 10.17 µg NP L -1 from the egg stage until 1 year of age did not induce testis-ova or lead to alter the sex ratios when compared with the control group (Ackermann et al, 2002).…”
Section: Sc Sc Szmentioning
confidence: 90%
“…In Nile tilapia, the mortality rate reached 40% after 7 days' exposure to 500 μgL -1 NP and 13.34% after 10 days from stopping exposure to NP (Ismail and Mahboub, 2016). In recent study carried out on zebrafish by Sun et al (2017) showed that NP can behave as a strong estrogen agonist at environmentally-relevant concentrations. The estrogenic effect of NP potentially disrupted the growth and sexual differentiation of zebrafish.…”
Section: Growth Performance and Survival Ratementioning
confidence: 99%
“…In addition, we found significantly delayed hatching time in the F1-2 following three consecutive generations of BaP exposure group (G1F1-3), except for F3. It is possible that marine medaka becomes resistant to BaP stress after long-term exposure [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty embryos (5 d pf ) per replicate were collected, homogenized and stored at -80 • C for subsequent RNA extraction, respectively. The Quantitative real-time PCR analysis was performed according to our previous study [21]. In brief, total RNA was extracted from three fish using Trizol reagent (Invitrogen).…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…The natural and synthetic steroid estrogens, 17b-estradiol (E2), and 17 a-ethinylestradiol (EE2), and alkyl phenols such as nonylphenol (NP) are among the most pervasive EDCs found in the aquatic environment (52)(53)(54)(55)(56). These chemicals are commonly found in sewage effluent discharged into rivers (57) and affect fish at concentrations, that range from 4.5 to 25 ng/L and 0.84 to 200 µg/L, respectively (58)(59)(60)(61). EE2, a primary estrogen component of most oral contraceptive pills, is discharged through municipal wastewater.…”
Section: Introductionmentioning
confidence: 99%